2020
DOI: 10.3389/fpsyt.2020.00809
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Functional and Structural Brain Connectivity in Humans Predicts Individual Social Comparison Orientation

Abstract: Social comparison orientation (SCO), the tendency to compare oneself with others, is universal, varies widely across individuals, and predicts important life and health outcomes. However, the neural mechanism underlying individual differences in SCO is still not well-understood. In the present study, we identified intrinsic neural markers of SCO in healthy young adults (n = 42) using a multimodal neuroimaging approach that included diffusion tensor imaging and resting-state functional MRI data. We found that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…The second approach of relating brain structure and function involves production of predictive models of cognition. Authors have used multiple regression (Ford and Kensinger, 2014 ; Jung and Kim, 2020 ; Putnam et al, 2008 ), canonical correlation analysis (Han et al, 2020 ; Lerman-Sinkoff et al, 2017 ), partial least squares (Dzafic et al, 2019 ), and connectome-based predictive modeling (Jiang et al, 2019 ). One study started with sparsity-constrained principal component regression in each modality, and the selected features of each modality were fed-forwards to a lasso analysis that integrated the models to a single model (Rasero et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The second approach of relating brain structure and function involves production of predictive models of cognition. Authors have used multiple regression (Ford and Kensinger, 2014 ; Jung and Kim, 2020 ; Putnam et al, 2008 ), canonical correlation analysis (Han et al, 2020 ; Lerman-Sinkoff et al, 2017 ), partial least squares (Dzafic et al, 2019 ), and connectome-based predictive modeling (Jiang et al, 2019 ). One study started with sparsity-constrained principal component regression in each modality, and the selected features of each modality were fed-forwards to a lasso analysis that integrated the models to a single model (Rasero et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have shown that task-independent neural measures such as resting-state fMRI can provide reliable and temporally stable measures of individual differences and predict specific behaviors (Horien et al, 2019;W. H. Jung & Kim, 2020).…”
Section: Resting State Functional Connectivity Between Anterior Insul...mentioning
confidence: 99%